Teaching work and academic capitalism. Turning the lenses to understand the daily work in the contemporary university (Praxis Educativa, 2021)
The introduction of the principles of New Public Management in higher education worldwide caused profound transformations in the systems, institutions and practices of the actors. University teaching work underwent significant modifications in its conditions, forms of organization and evaluation. In this writing we focus on the forms that teaching work assumes in the context of academic capitalism from the understanding of what circulates in the daily life of the university. For this, fragments of interviews and extracts of informal conversations with professors of public universities in Argentina are recovered. Issues such as the material and symbolic recognition of the work done, the relationships between teaching work and daily life, the question of working time as the computer of life time, the intensification of tasks and the growing demand for permanent availability are addressed.